Dual protein kinase and nucleoside kinase modulators for rationally designed polypharmacology. Issue 1 (December 2017) - Hammam, Kahina; Saez-Ayala, Magali; Rebuffet, Etienne; Gros, Laurent; Lopez, Sophie; Hajem, Berengere; Humbert, Martine; Baudelet, Emilie; Audebert, Stephane; Betzi, Stephane; Lugari, Adrien; Combes, Sebastien; et al.
Abstract Masitinib, a highly selective protein kinase inhibitor, can sensitise gemcitabine-refractory cancer cell lines when used in combination with gemcitabine. Here we report a reverse proteomic approach that identifies the target responsible for this sensitisation: the deoxycytidine kinase (dCK). Masitinib, as well as other protein kinase inhibitors, such as imatinib, interact with dCK and provoke an unforeseen conformational-dependent activation of this nucleoside kinase, modulating phosphorylation of nucleoside analogue drugs. This phenomenon leads to an increase of prodrug phosphorylation of most of the chemotherapeutic drugs activated by this nucleoside kinase. The unforeseen dual activity of protein kinase inhibition/nucleoside kinase activation could be of great therapeutic benefit, through either reducing toxicity of therapeutic agents by maintaining effectiveness at lower doses or by counteracting drug resistance initiated via down modulation of dCK target. Masitinib is a protein kinase inhibitor that sensitises refractory pancreatic adenocarcinoma cells to treatment with the nucleoside analog gemcitabine. Here the authors show that Masitinib activates deoxycytidine kinase to enhance phosphorylation of nucleoside analogue pro-drugs, increasing their potency.